Analysis of Platelet Count on Liver Cirrhosis Patients Based on Child-Pugh Classification - Renanda Maulidya Fadyla; Rahmat Bakhtiar; RR. Ignatia Sinta Murti (Jurnal Sains dan Kesehatan, 2021)
Liver cirrhosis is described as a diffused pathological process which marked with fibrosis and architectural changes of normal liver that becomes an abnormal nodular structure. Liver cirrhosis is caused by chronic liver disease of virus nor non virus. Thrombocytopenia is a hematology abnormality which frequently found on liver cirrhosis patients. Severity level and prognosis of liver cirrhosis can be determined by Child-Pugh classification. This research aims to know the difference of mean platelet count on liver cirrhosis patients based on Child-Pugh classification. It applied analytic observational method with cross-sectional design. The data was taken from medical records of patients at Abdul Wahab Sjahranie Hospital in Samarinda of 2018-2020 period. Statistical analysis was using Kruskal-Wallis test. The results showed liver cirrhosis patients in Child-Pugh C is at most. Mean platelet count of liver cirrhosis with Child-Pugh A is 73.250/?l, Child-Pugh B is 126.370/?l, and Child-Pugh C is 148.375/ ?l. Based on statistical test, the score p = 0,19 (p > 0,05), there are no differences of mean platelet count among the three Child-Pugh classifications.